Physical characterization and compression tests of one leaf stone masonry walls - Almeida, C (2012)
Most of the ordinary buildings of Porto. Portugal, build up to early 20th century are made of one-leaf granite walls with large stone blocks. The influence of stones' shape, internal voids and mortar on the mechanical characteristics has been studied. Aiming at assessing the behavior of these structures, a number of wall panels retrieved from a building were tested in laboratory. Compression tests were performed to evaluate the wall response, both in original state and after injection with lime mortar. The results show a relatively low stiffness, which increased about three times after injection.